Fear learning and aversive stimuli differentially change excitatory synaptic transmission in perisomatic inhibitory cells of the basal amygdala - Veres, Judit M.; Fekete, Zsuzsanna; Müller, Kinga; Andrasi, Tibor; Rovira-Esteban, Laura; Barabas, Bence; Papp, Orsolya I.; Hajos, Norbert (Frontiers in Cellular Neuroscience, 2023)
Inhibitory circuits in the basal amygdala (BA) have been shown to play a crucial role in associative fear learning. How the excitatory synaptic inputs received by BA interneurons are influenced by memory formation, a network parameter that may contribute to learning processes, is still largely unknown. Here, we investigated the features of excitatory synaptic transmission received by the three types of perisomatic GABAergic interneurons upon different behavioral challenges. Acute slices were prepared from transgenic mice: one group received tone presentation only (conditioned stimulus, CS group), the second group was challenged by mild electrical shocks unpaired with the CS (unsigned unconditioned stimulus, unsigned US group) and the third group was presented with the CS paired with the US (signed US group). We found that excitatory synaptic inputs (miniature excitatory postsynaptic currents, mEPSCs) recorded in distinct interneuron types in the BA showed plastic changes with different patterns. Parvalbumin (PV) basket cells in the unsigned US and signed US group received mEPSCs with reduced amplitude and rate in comparison to the only CS group. Coupling the US and CS in the signed US group caused a slight increase in the amplitude of the events in comparison to the unsigned US group, where the association of CS and US does not take place. Excitatory synaptic inputs onto cholecystokinin (CCK) basket cells showed a markedly different change from PV basket cells in these behavioral paradigms: only the decay time was significantly faster in the unsigned US group compared to the only CS group, whereas the amplitude of mEPSCs increased in the signed US group compared to the only CS group.Excitatory synaptic inputs received by PV axo-axonic cells showed the least difference in the three behavioral paradigm: the only significant change was that the rate of mEPSCs increased in the signed US group when compared to the only CS group. These results collectively show that associative learning and aversive stimuli unpaired with CS cause different changes in excitatory synaptic transmission in perisomatic interneuron types, supporting the hypothesis that they play distinct roles in the BA network operations upon pain information processing and fear memory formation.